Prediction of the differences in tumor mutation burden between primary and metastatic lesions by radiogenomics. Issue 1 (11th November 2021) - Hoshino, Isamu; Yokota, Hajime; Iwatate, Yosuke; Mori, Yasukuni; Kuwayama, Naoki; Ishige, Fumitaka; Itami, Makiko; Uno, Takashi; Nakamura, Yuki; Tatsumi, Yasutoshi; Shimozato, Osamu; Nagase, Hiroki
Abstract: Tumor mutational burden (TMB) is gaining attention as a biomarker for responses to immune checkpoint inhibitors in cancer patients. In this study, we evaluated the status of TMB in primary and liver metastatic lesions in patients with colorectal cancer (CRC). In addition, the status of TMB in primary and liver metastatic lesions was inferred by radiogenomics on the basis of computed tomography (CT) images. The study population included 24 CRC patients with liver metastases. DNA was extracted from primary and liver metastatic lesions obtained from the patients and TMB values were evaluated by next‐generation sequencing. The TMB value was considered high when it equaled to or exceeded 10/100 Mb. Radiogenomic analysis of TMB was performed by machine learning using CT images and the construction of prediction models. In 7 out of 24 patients (29.2%), the TMB status differed between the primary and liver metastatic lesions. Radiogenomic analysis was performed to predict whether TMB status was high or low. The maximum values for the area under the receiver operating characteristic curve were 0.732 and 0.812 for primary CRC and CRC with liver metastasis, respectively. The sensitivity, specificity, and accuracy of the constructed models for TMB status discordance were 0.857, 0.600, and 0.682, respectively. Our results suggested that accurate inference of the TMB status is possible using radiogenomics. Therefore, radiogenomics could facilitate the diagnosis, treatment, and prognosis of patients with CRC in the clinical setting. Abstract : This study evaluated the status of tumor mutation burden (TMB) in primary and liver metastatic lesions in patients with colorectal cancer using radiogenomics. In 7 out of 24 patients (29.2%), the TMB status differed between the primary and liver metastatic lesion. Radiogenomic analysis was used to accurately predict whether TMB status was high or low.